Kreativitas Tari dengan Permainan Kentongan pada Kegiatan Ektrakurikuler di SMKN 1 Banjarbaru - Dewi Rukmini Sulistyawati; Suwarjiya Suwarjiya; Anisa Rizky Septiana (Journal on Education, 2023)
Sensitivity to rhythm and tempo is important in learning dance. When sensitivity is lacking, disharmony will appear in the dance. As happened in extracurricular activities at SMKN 1 Banjarbaru. Even though students take part in mint-based activities, there are still many students who are less sensitive to rhythm and tempo. Students are able to memorize dance movements, but they are often loose and not in accordance with the rhythm of the music. For this reason, activities are needed that give special emphasis related to rhythm and tempo. The purpose of this study is to describe the process and results of dance creativity by playing kentongan. Qualitative descriptive research method. The results showed that the creativity process was carried out through the stages of exploration, improvisation, and composition. In the exploration stage, students try to hit the kentongan with several different rhythms and tempos. Students also try to find some movements that can be done with their hands while hitting the kentongan. The improvisation stage is done by trying to combine the appropriate motion and tempo. The composition stage was carried out by composing and sequencing several movements while hitting the kentongan that had been obtained. The results obtained, group one was able to make five tempos and two tempo variations, five movements and three variations of movements, and four floor patterns. Group two was able to make five tempos and three tempo variations, five movements and three variations of movements, and four floor patterns.